Repackaging the Indonesiana collection as a transformation of digital learning resources - Dini Suhardini; Isma Anggini Saktiani; Lisna Nurhalisma (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
Collections are the main element to meet the information needs of college library users. One of the collections owned is the Indonesianna collection, which is a collection about Indonesia covering culture, arts, customs, and literature. This collection is not only presented in printed form but also in digital display, which is the result of repackaging with the hope that the digital form of the Indonesiana collection can be used as a digital learning resource and can make it easier for users to utilize the information contained in the collection. This research aims to discover the process of repackaging Indonesian collections as a form of transformation of digital learning resources in the UPI Library. This study used a qualitative descriptive method with data collection methods through interview techniques and literature study. Repackaging activities through media transfer from print to digital format so that it is easily accessible and avoids loss of information content. There are 2,505 Indonesiana collections in the UPI Library, but not all collections have been repackaged in digital format. The stages of repackaging the Indonesiana collection at the UPI Library include collection selection/selection, receiving and checking, data recapitulation/analysis, scanning (formatting), and uploading the scanned results as a product. To ease information retrieval for digital format, the patrons can access the Indonesiana collection through E-Lib UPI. AbstrakKoleksi menjadi unsur utama untuk memeuhi kebutuhan informasi pemustaka perpustakaan perguruan tinggi. Salah satu koleksi yang dimiliki adalah koleksi Indonesiana yaitu koleksi tentang Indonesia meliputi, budaya, seni, adat istiadat dan kesusastraan. Koleksi ini tidak hanya disajikan dalam bentuk cetak tetapi juga tampilan digital yang merupakan hasil repackaging dengan harapan bentuk digital dari koleksi Indonesiana ini dapat digunakan sebagai sumber belajar digital serta dapat mempermudah pemustaka dalam memanfaatkan informasi yang terkandung didalam koleksi tersebut. Tujuan dari penelitian ini adalah untuk mengetahui proses repackaging koleksi Indonesia sebagai wujud transformasi sumber belajar digital di Perpustakaan UPI. Penelitian ini menggunakan metode deskriptif kualitatif dengan metode pengumpulan data melalui teknik wawancara serta studi pustaka. Kegiatan repackaging melalui alih media dari format cetak ke digital agar mudah diakses dan terhindar dari hilangnya kandungan informasi di dalamnya. Koleksi Indonesiana yang ada di Perpustakaan UPI saat ini berjumlah 2.505 judul tapi belum semua koleksinya di repackaging dalam format digital. Tahapan repackaging koleksi Indonesiana di Perpustakaan UPI meliputi kegiatan pemilihan/seleksi koleksi, penerimaan dan pengecekan, merekap data/analisis, scanning (alih format), melakukan unggah hasil scan sebagai produk. Untuk memudahkan penelusuran format digital, akses dilakukan dalam E-Lib UPI.Kata Kunci: E-Lib UPI; kemas ulang informasi; koleksi Indonesiana; sumber belajar digital; transformasi digital